Dadi Jeksa; Adaptation of Serat Jayengbaya to Dance Film - Deny Tri Ardianto; Bedjo Riyanto; Sayid Mataram; Mohd Asyiek Mat Desa (Mudra Jurnal Seni Budaya, 2022)
As a law enforcement officer, a prosecutor plays an important role in investigating a case or prosecuting a suspect. However, in recent years, several prosecutors were found involved in a number of corruption cases in Indonesia. This phenomenon is not a new one. In Serat Jayengbaya written by R.Ng. Ronggowarsito, especially in the song Dadi Jeksa, the behavior and life of prosecutors in the past are depicted as a profession full of intrigue and manipulation. This phenomenon inspired the making of a dance film adapted from Dadi Jeksa song. Using a Research and Development (RnD) approach, this film was designed to use movements based on contemporary dance as a means of its story telling. This film represents the culture and perspective of the Indonesian people in viewing legal issues. After the film was presented at various festivals and exhibitions, positive responses were obtained from various parties. The appreciation received mainly focused on the film’s creative storytelling and visualization in presenting a depiction of law enforcement dynamics in Indonesia.